Orchid mantises and other extreme insect adaptations - Wheeler-Toppen, Jodi (North Mankato, MN Capstone Press, a Capstone imprint, 2015)
Explores various extreme insect adaptations throughout the world, including meganosed flies, assassin bugs, and bombardier beetles
Science (Insects)
a gift from book africa
Keywords: Adaptation (Biology) -- Juvenile literature; Insects -- Adaptation -- Juvenile literature; Insects -- Physiology -- Juvenile literature